Energy Transfer Mechanisms in Mitochondria - Kemeny, Gabor (1974)
The problem of free energy transfer and transduction in mitochondria is reviewed from the point of view of conservative and dissipative mechanisms. Excited states are inherently dissipative and are not considered viable possibilities. If the free energy is already a local minimum and present in the form of potential energy, conservative transfer is possible within a properly designed medium. The design features are compatible with what is known about mitochondria.